Alcohol-induced hemiplegia hypoglycemia in end stage renal disease patient: a case report - Juliarta, I Gede; Noverina, I. G. A. Anggia (International Journal of Advances in Medicine, 2022)
Hypoglycemia is one of the problems that often makes patients come to the emergency department. Generally, patients come with complaints of weakness, shaking, cold sweats, decreased consciousness. Hemiplegia is a rare clinical presentation in hypoglycemic patients. A case 44-year-old male comes to the emergency department with symptoms of weakness in the right half of the body and slurred speech noticed when he wakes up. History of drinking alcohol 1 day before. Based on history and physical examination, the patient is suspected of having stroke. Laboratory examination revealed that the patient had severe hypoglycemia. Administration of 50 ml of D40 fluid resulted in significant improvement in symptoms, and within 3 hours the neurological deficit disappeared. The head CT scan results were within normal limits. This case described hemiplegia which is a rare symptom of hypoglycemia, so that blood sugar checks are important in patients with suspected stroke.